Measurement of the differential cross section for events with large total transverse energy in p(p)over-bar collisions at root s=1.8 TeV - Abe, F; Akimoto, H; Akopian, A; Albrow, MG; Amadon, A; Amendolia, SR; Amidei, D; Antos, J; Aota, S; Apollinari, G; Arisawa, T; Asakawa, T; et al. (1998)
We present a measurement of the differential cross section dσ/dΣETjet for the production of multijet events in pp̄ collisions where the sum is over all jets with transverse energy ETjet > ETmin. The measured cross section for events with ΣETjet > 320 GeV is compared to (αs3) perturbative QCD predictions and QCD parton shower Monte Carlo predictions. The agreement between the (αs3) predicted and observed event rates is reasonable for ETmin = 100 GeV, but poorer for ETmin = 20 GeV.